Network administrator : Netware 4.1. - Simpson, Ted L. (Course Technology, 1997)
This book is about: Networking Basics; Microcomputer hardware; Designing the Network; Planning the Novell Directory Services (NDS) Directory Tree; Planning the Network File Systems...